2022
DOI: 10.1038/s41467-022-29671-0
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking bimetallic active sites via a desalination strategy for photocatalytic reduction of atmospheric carbon dioxide

Abstract: Ultrathin two-dimensional (2D) metal oxyhalides exhibit outstanding photocatalytic properties with unique electronic and interfacial structures. Compared with monometallic oxyhalides, bimetallic oxyhalides are less explored. In this work, we have developed a novel top-down wet-chemistry desalination approach to remove the alkali-halide salt layer within the complicated precursor bulk structural matrix Pb0.6Bi1.4Cs0.6O2Cl2, and successfully fabricate a new 2D ultrathin bimetallic oxyhalide Pb0.6Bi1.4O2Cl1.4. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…The unlocked larger surface area, rich bimetallic active sites, and faster carrier dynamics within Pb 0.6 Bi 1.4 O 2 Cl 1.4 layers significantly enhance the photocatalytic efficiency for atmospheric CO 2 reduction. 142 Ultrathin 2D photocatalysts also display effective regulation of product selectivity for CO 2 reduction. Atomically thin, singlecrystalline InVO 4 sheets exposing (110) facets with a uniform thickness of B1.5 nm possess high selectivity for transformation of CO 2 to CO in the presence of water vapor, relative to the referred nanocubes with an exposed (100) facet.…”
Section: Photocatalytic Conversion Of Co 2 Into Renewable Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unlocked larger surface area, rich bimetallic active sites, and faster carrier dynamics within Pb 0.6 Bi 1.4 O 2 Cl 1.4 layers significantly enhance the photocatalytic efficiency for atmospheric CO 2 reduction. 142 Ultrathin 2D photocatalysts also display effective regulation of product selectivity for CO 2 reduction. Atomically thin, singlecrystalline InVO 4 sheets exposing (110) facets with a uniform thickness of B1.5 nm possess high selectivity for transformation of CO 2 to CO in the presence of water vapor, relative to the referred nanocubes with an exposed (100) facet.…”
Section: Photocatalytic Conversion Of Co 2 Into Renewable Fuelsmentioning
confidence: 99%
“…The unlocked larger surface area, rich bimetallic active sites, and faster carrier dynamics within Pb 0.6 Bi 1.4 O 2 Cl 1.4 layers significantly enhance the photocatalytic efficiency for atmospheric CO 2 reduction. 142…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
“…[19] From reported works and this study, it can be found that the adsorption and activation of CO 2 on the surface of photocatalysts would be influenced by the competitive O 2 adsorption in atmospheric CO 2 reduction process. [18,19] Therefore, we further added different amounts of O 2 in pure CO 2 to study the effect of O 2 on the selectivity of products in PCR (Figure S23). When the volume of added oxygen increased from 0 to 10 mL, the yield of CH 4 decreased and the yield of CO increased, which confirmed that the presence of O 2 changed the selectivity of products in PCR, which is consistent with previous reports.…”
Section: Forschungsartikelmentioning
confidence: 64%
“…Excessive emissions of CO 2 can lead to many intractable environmental issues. [1][2][3][4][5] In this context, in September 2020, our country put forward "peaking carbon emissions by 2030 and achieving carbon neutrality by 2060". 6 Moreover, the "double carbon" target was incorporated into the general layout of ecological civilization construction, aiming to solve a series of problems caused by the greenhouse effect.…”
Section: Introductionmentioning
confidence: 99%